SIFAT FISIK DAN MEKANIK PAPAN ORIENTED STRAND BOARD DARI API-API PUTIH (Avicennia marina) DAN BAMBU AMPEL (Bambusa vulgaris) - Santoso, Eko; Dirhamsyah, M; Yani, Ahmad (JURNAL HUTAN LESTARI, 2018)
The objective of this research is to know the effect of raw material type and composition on physical and mechanical properties of Orient Strand Board of Avicennia marina and Bambusa vulgaris, to know the type and composition of the best materials that meet JIS A 5908 - 2003. The materials used in this research are Avicennia marina and Bambusa vulgaris, phenol formladehida (PF) adhesives and liquid paraffin. The treatment in this research is raw material consisting of Avicennia marina/Bambusa vulgaris, Bambusa vulgaris/Avicennia marina, Avicennia marina and Bambusa vulgaris, with raw material composition 50/50%, 60/40% and 70/30%. OSB boards are made measuring 30 cm x 30 cm x 1 cm with a target density of 0,75 gr/cm3 forged hot with a temperature of 160 Âº C for 7 minutes. The parameters tested in this study include physical properties (density test, moisture content, swelling in thickness and water absorption), mechanical properties (modulus of elasticity, modulus of rupture, internal bonding and screw holding power) and retention strength. The results showed that the type of raw material had an effect on the moisture content, MOE, MOR, IB and screw holding power, but did not affect the density, water absorption and , swelling in thickness. Treatment of raw material composition influenced moisture, MOE and MOR, but did not affect the density, water absorption, swelling in thickness, IB and screw holding power. The interaction of both factor and raw material composition influenced the value of water content, water absorption, swelling in thickness, MOE and MOR, but did not affect the density, IB and screw holding power. Based on the results of the research can be seen that the mixture Bambusa vulgaris/Avicennia marina with 70/30% composition is the best OSB and meets the standard JIS A 5908-2003 Base Particleboard Type 24-10. Keywords: Avicennia marina, Bambusa vulgaris, Oriented Strand Board, Physical Properties and Mechanical.